Urgency of Spatial Planning of the Mataram City Library and Archives Office in Increasing Interest In Visiting Libraries in Mataram City - Iwin Ardyawin (Literatify : Trends in Library Developments, 2023)
The primary issue in this study is how the Mataram city library's spatial planning affects the number of visitors who are interested in Mataram City’s library. In order to increase the interest of visiting users in the city of Mataram, it will be discussed how the roles and limitations of the Mataram city library's physical layout affect its services. The research method used in this study was descriptive qualitative research, and the primary data source was interviews and field observations. Secondary data sources included documentation, journals, websites, scripts, and other sources, as well as results from other types of research. The study's findings show how the Mataram city library service can increase the interest of readers who are visiting the city by using a variety of elements, including space (layout), library rooms, facilities, ventilation, and color, while the library service's challenges must be overcome. There aren't many rooms because The Library Service of Mataram City is still in the planning or development stage.